Analysis of the relationship between anxiety symptoms and temporomandibular disorder in undergraduate dental students - Letícia Lima Morais Carvalho; Izabela da Costa; Ariane Aurélia Teixeira Carvalhais; Ronaldo Luís Almeida de Carvalho; Jean Soares Miranda (Brazilian Dental Science)
Objective: To evaluate, through the application of validated questionnaires, whether the level of anxiety symptoms was associated with the occurrence of painful Temporomandibular Disorders (TMDs) in undergraduate dental students. Material and Methods: To check the occurrence of symptoms of anxiety disorders the GAD-7 (Generalized Anxiety Disorder – 7) questionnaire was applied and to diagnose TMDs the DC/TMD (Diagnostic Criteria for TMDs) was administered to 60 patients. Participants were divided into two groups: control (Co), composed of students without TMD diagnosis (n=30), and experimental group (Exp), composed of students with a TMD diagnosis (n=30). The acquired data underwent descriptive analysis and statistical treatment using chi-square or Fisher’s exact tests. Results: The results showed a significant relationship between moderate and severe anxiety levels with the occurrence of TMDs (p < 0.001), not being related to a specific type of these disorders (muscular and/or joint) (p = 0.071). Regarding sex, it was observed that it does not influence the occurrence of TMDs (p = 0.778). However, sex was related to anxiety levels (p < 0.001), with males in our study being associated with moderate and severe levels of anxiety symptoms. Conclusion: It was concluded that anxiety is associated with the occurrence of painful TMDs in dental students, with moderate and severe levels of anxiety symptoms being more prevalent in individuals with TMD.